Counselors’ experience with disaster survivors of natural disasters: A descriptive phenomenological study - Zakaria, Mohd. Zaliridzal; Zakaria, Noor Syamilah; Baharudin, Dini Farhana; Krauss, Steven Eric; Madon, Zainal; Subarimaniam, Neerushah (Human Resource Management Academic Research Society, 2021)
Disaster survivors are individuals who are literally survived in the aftermath of disaster situations. They are dislocated from their affected homes to evacuation centers; and forced to leave behind all belongings. Due to the characteristics of disasters that are sudden and catastrophic, disaster survivors often experience substantial symptoms of distress and respond with psychological and psychosocial reactions. This qualitative research was conducted using a descriptive phenomenological study approach to explore, understand, and describe the experience of counselors during natural disasters in Malaysian. The authors were the primary instrument for data collection and analysis. Data included field notes and individual semi-structured in-depth interviews. The authors developed coding categories using ATLAS.ti. The themes that emerged were refined, and became the major and subthemes for this research. This research found that the experience gained from the disaster survivors during the disaster situations has developed the understanding and addressing the complexity of satisfying disaster survivors’ critical needs during natural disasters. It was also informed that providing crisis support during natural disaster has brought plethora of experiences and knowledge that should be shared with other counselors in Malaysia.